Queue management system with automatic assign queue feature using geofencing - Azri, Luqman Syahmi; Arshad, Mohamad Asrol (College of Computing, Informatics, and Mathematics, 2025)
The increasing inefficiencies in traditional queue management systems, particularly prolonged waiting times and manual registration processes, necessitate innovative solutions. This study introduces a Queue Management System with an Automatic Assign Queue Feature Using Geofencing to enhance service efficiency by automatically assigning queue numbers based on a user’s real-time location. By utilizing geofencing, the system detects a user’s arrival at a service provider’s location and assigns a queue number, reducing manual intervention. The system follows the Waterfall Model methodology, covering five phases: Requirement Analysis, Application Design, Implementation, Testing, and Documentation. The system integrates Flutter for mobile development, Laravel for the backend, MySQL for data management, and Google Maps API for geofencing-based queue automation. Functional and accuracy testing were conducted, with results confirming a 100% success rate in queue number assignment. Findings indicate that the system significantly reduces waiting times and improves queue distribution efficiency, benefiting both customers and service providers. Future enhancements could include multi-location service provider integration and cross-platform support for iOS to ensure broader accessibility.